Complex urban environments provide Apis mellifera with a richer plant forage than suburban and more rural landscapes. Issue 11 (8th November 2022) - Fox, Graeme; Vellaniparambil, Latha R.; Ros, Loreto; Sammy, Joshua; Preziosi, Richard F.; Rowntree, Jennifer K.
Abstract: Growth in the global development of cities, and increasing public interest in beekeeping, has led to increase in the numbers of urban apiaries. Towns and cities can provide an excellent diet for managed bees, with a diverse range of nectar and pollen available throughout a long flowering season, and are often more ecologically diverse than the surrounding rural environments. Accessible urban honeybee hives are a valuable research resource to gain insights into the diet and ecology of wild pollinators in urban settings. We used DNA metabarcoding of the rbcL and ITS2 gene regions to characterize the pollen community in Apis mellifera honey, inferring the floral diet, from 14 hives across an urban gradient around Greater Manchester, UK. We found that the proportion of urban land around a hive is significantly associated with an increase in the diversity of plants foraged and that invasive and non‐native plants appear to play a critical role in the sustenance of urban bees, alongside native plant species. The proportion of improved grassland, typical of suburban lawns and livestock farms, is significantly associated with decreases in the diversity of plant pollen found in honey samples. These findings are relevant to urban landscape developers motivated to encourage biodiversity and bee persistence, in line with global bio‐food security agendas. Abstract : Using 2‐barcode metabarcoding, we identified the floral diet of honeybees across an urban gradient in Greater Manchester. Bees foraging in more urbanized environments had access to a greater diversity of plants than those foraging in more rural environments. Non native and naturalized species comprised an important part of the diet of urban foraging bees along side native species.